Konten Kreatif yang Menarik secara Visual dan Emosional sebagai Upaya Meningkatkan Engagement dan Loyalitas Pelanggan Oishi Chicken Fillet - Kurnilia, Riska Elsa; Triamita, Viola Yuliana; Atika, Lia Nur; Pramesti, Adilla Puspa; Zuhri, Syaroffidin; Shobari, Moh Khakim; Ramelan, Muhammad Wahyu; Fatmawatie, Naning; Ardika, Rendi; Aditya, Tony; Sugiarto, Suprihantosa (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
Oishi Chicken Fillet Kediri faces challenges in increasing customer engagement and loyalty amidst increasingly tight culinary business competition. This community service activity aims to develop creative content that is visually and emotionally appealing to increase brand appeal and strengthen relationships with customers. Using the Participatory Action Research (PAR) method, this activity actively involves the owner and team of Oishi Chicken Fillet in the process of identifying problems, formulating strategies, and implementing solutions. The stages of the activity include food photography and videography workshops, emotion-based storytelling strategy training, and assistance in implementing digital marketing through social media. The results of the activity showed an increase in customer engagement of up to 40%, marked by more active social media interactions, and an increase in customer loyalty of 25%, seen from the increasing number of loyal customers. The PAR approach is effective in creating solutions based on real needs while empowering the business community to grow sustainably.